Influence of Profitability, Liquidity, and Company Size on Profit Growth in A Consumer Non-Cyclical Company - Regina Amanda Putri; Florencia Irena Lawita; Gerard Hoffen Hadiwidjaja (Universitas Pelita Harapan, 2024)
This research aims to examine the effect of profitability, liquidity and company size on profit growth in non-cyclical consumer sector companies listed on the IDX in 2019 - 2022. This research uses a quantitative approach. The method used in sampling in this research was purposive sampling. The population in this research is the annual financial reports of non-cyclical consumer sector companies listed on the IDX for 2019 - 2022, thus obtaining a sample of 28 companies. The research results show that profitability has a significant influence on profit growth. But liquidity and company size have no effect on profit growth.